Murder makes scents - Brecher, Christin (Brecher, Christin. Nantucket candle maker mystery., 2020)
Stella and her globe-trotting mom, Millie, have come home from a perfume industry conference in Paris, where their trip was marred by witnessing the stabbing death of a young man. It<U+2019>s a relief for Stella to be back on her picturesque island, with the comforting company of her cat, Tinker. But lingering danger may have followed them back across the ocean. After someone breaks into her candle store, the Wick & Flame, Stella starts feeling spooked. And just as things threaten to ignite, Millie suffers a blow to the head. Stella receives an anonymous note claiming that her mother smuggled a secret formula out of France<U+2014>and threatening her life if it isn<U+2019>t returned. Now Stella<U+2019>s picked up the scent of a cold-hearted criminal and an intriguing puzzle, and things are about to get wicked . . .